Antiplatelet resistance in outpatients with monitored adherence. (November 2014) - Walter, Philipp N.; Tsakiris, Dimitrios A.; Romanens, Michel; Arnet, Isabelle; Hersberger, Kurt E.
Abstract Antiplatelet resistance with aspirin and clopidogrel has been associated with clinical, cellular and pharmacogenetic factors; and non-adherence has been considered as a major contributor to resistance in outpatients. We aimed at assessing factors to resistance when adherence to the antiplatelet drugs and all other oral solid drugs was controlled for. In a pilot study, we tested arachidonic acid and/or ADP-induced in vitro platelet aggregation of 82 outpatients with chronic aspirin and/or clopidogrel treatment before and after a one-week period of measuring the patient's adherence with the polymedication electronic monitoring system (POEMS). Resistance was found in 20% (aspirin; n = 69) and 25% (clopidogrel; n = 32) of the patients after monitored adherence. Mean platelet aggregation was not (aspirin) or non-significantly (clopidogrel) lowered when compared to baseline. Diabetes mellitus and inflammation were consistently associated with resistance to both drugs, but CYP2C19 polymorphisms could not be confirmed as predictors of clopidogrel response. Electronically compiled multidrug dosing histories allowed the concomitant intake of high-dose lipophilic statins to be identified as a risk factor of impaired response to clopidogrel and revealed that exposure to further potential drug–drug interactions (DDIs) was too low for analysis. Multidrug adherence monitoring allowed thus dismissing non-adherence as a major contributor to resistance and inter-individual response variability in an outpatient setting. Additionally, it allowed analysing the impact of DDIs according to the actual exposure to the potentially interfering drugs. Further studies based on this methodology are essential to prevent misleading results due to incomplete adherence and gain additional insight into the impact of timing adherence on antiplatelet drug response.